Use elimination to find the solution to the system of equations.

Accepted Solution

Answer:  option B.Step-by-step explanation: You can apply the elimination method: - Multiply the first equation by -7 and the second equation by 3. - Add both equations to cancel out the variable y. - Solve for x [tex]\left \{ {{(-7)9x+3y=(-39)(-7)} \atop {(3)(4x+7y)=(-57)(3)}} \right.\\\\\left \{ {{-63x-21y=273} \atop {12x+21y=-171}} \right.\\-------\\-51x=102\\x=-2[/tex] - Substitute x=-2 into any of the original equations ans solve for y. Then: [tex]9(-2)+3y=-39\\-18+3y=-39\\3y=-21\\y=-7[/tex]